2012
DOI: 10.1074/jbc.m112.372474
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar Structure and Charge Determine the Interaction of Polyglutamine Protein Aggregates with the Cell Surface

Abstract: Background: Polyglutamine aggregates can be internalized by mammalian cells and gain access to the cytoplasmic compartment, but the properties of the aggregates and cell surface that mediate these processes are unknown. Results: Introduction of net negative charge and disruption of fibrillar structure greatly reduced the capacity of polyglutamine aggregates to bind and be internalized by mammalian cells. Conclusion: Aggregate uptake is influenced by the structure and net charge of aggregates and is mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 24 publications
(23 reference statements)
1
52
1
1
Order By: Relevance
“…In the case of aggregating peptides, several amyloids have been proposed to be recognized by other membrane receptors, mostly of the TLR and scavenger families (26 -31). In addition, it has been shown that amyloid conformation could determine the membrane adhesion of small oligomers (63). Our results indicate that strongly aggregating peptides could reach a size that favors interaction with cell membranes regardless of their amyloid or amorphous organization, although the nature of this interaction remains to be investigated.…”
Section: Discussionmentioning
confidence: 81%
“…In the case of aggregating peptides, several amyloids have been proposed to be recognized by other membrane receptors, mostly of the TLR and scavenger families (26 -31). In addition, it has been shown that amyloid conformation could determine the membrane adhesion of small oligomers (63). Our results indicate that strongly aggregating peptides could reach a size that favors interaction with cell membranes regardless of their amyloid or amorphous organization, although the nature of this interaction remains to be investigated.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, we assessed the functional properties of HttEx1Q48 fibrils formed in the absence or presence of Hsc70 using the nucleation assay we established in reporter cell lines (U2OS cells) expressing soluble HttEx1Q25-ChFP (10,34). The endogenous HttEx1Q25-ChFP redistributed into fluorescent foci in 50% of cells exposed to HttEx1Q48 fibrils formed in the absence of Hsc70, whereas only 22% of cells exposed to identical concentrations of HttEx1Q48 fibrils formed in the presence of Hsc70 exhibited puncta (Fig.…”
Section: G and H)mentioning
confidence: 99%
“…In Vivo Seeding Assays-We compared the nucleation capacities of HttEx1Q48 fibrils assembled in the absence or the presence of Hsc70 using the assay we established in reporter cell lines (10,34). In summary, U2OS cells stably expressing soluble mCherry fluorescent protein fused to HttEx1Q25 (HttEx1Q25-ChFP) were grown in McCoy's 5A medium supplemented with 10% FBS, 2 mM glutamine, 100 units/ml penicillin, 100 g/ml streptomycin, and 500 g/ml G418 on poly-L-lysine-coated coverslips.…”
Section: Expression and Purification Of Recombinant Polypeptides And mentioning
confidence: 99%
“…The polyQ expansion causes Htt to form amyloids in neurons [79]. Expanded polyQ peptide amyloids gain access to the cytoplasm of a variety of mammalian cells upon introduction to the culture medium [80]. The fibrils that are taken into the cell can induce the aggregation of other proteins with polyQ tracts, and this misfolding is maintained for multiple passages, implying the aggregates formed from endogenously expressed protein can also seed further intracellular misfolding and aggregation, similar to yeast prions [81].…”
Section: Prion-like Properties Of the Huntingtin Proteinmentioning
confidence: 99%
“…Cells can therefore take up Htt, but cell-to-cell transfer of these aggregates appears relatively inefficient compared to the other aggregationprone proteins discussed above. The exact amino acid sequence surrounding the polyglutamine tract can influence the propensity of uptake, as fibrils composed of KKQ44KK bind cells much more readily than fibrils formed from a fragment of the Htt protein [80]. Thus, polyQ fibrils can be taken into cells and seed the aggregation of other polyQcontaining proteins, but this phenomena depends on the sequences that flank this tract.…”
Section: Prion-like Properties Of the Huntingtin Proteinmentioning
confidence: 99%